PERAMALAN INDEKS HARGA KONSUMEN KABUPATEN BANYUMAS DENGAN METODE SARIMA - Arini Rizky Wahyuningtyas; Wahyu Putri Pratiwii; Rochdi Wasono; Tiani Wahyu Utami (Jurnal Litbang Edusaintech, 2022)
The CPI is used as an indicator to determine the inflation rate that can describe economic developments in a region. Uncontrolled inflation will have a direct impact on economic conditions. Therefore, it is necessary to have a method to predict the CPI so that the government can determine the right policy so that the economic condition of the community becomes more stable and improves. In this study, CPI forecasting in Banyumas Regency will be carried out using the SARIMA method. The purpose of this study is to predict the CPI in the future. This study uses CPI data from Banyumas Regency from January 2014 to August 2021 with 92 data. The results show that the SARIMA (1,1,1)(0,1,1)12 model is the right model for forecasting the CPI in Banyumass Regency. Forecasting the CPI for Banyumas Regency for the next 12 months using the SARIMA (1,1,1)(0,1,1)12 method shows a trend pattern that tends to increase or inflation will not be so high.